Antibacterial effectiveness of belimbing wuluh leaf extract (Averrhoa bilimbi L.) and meniran herb (Phyllanthus niruri L.) against Staphylococcus epidermidis - Ariaditya Wibowo; Agnes Yuliana; Dwi Puspita Sari (Farmasains : Jurnal Farmasi dan Ilmu Kesehatan, 2024)
Acne is an inflammatory condition of the skin which is commonly called polysebaceous which is caused by the Staphylococcus epidermidis bacteria. Meniran herbs and starfruit leaves contain compounds that are used as antibacterials, namely tannins, flavonoids and saponins. The purpose of this study was to determine the effectiveness of the antibacterial combination of star fruit wuluh leaf extract (Averrhoa bilimbi L.) and meniran herb (Phyllanthus niruri L.) as an antibacterial in inhibiting the growth of the Staphylococcus epidermidis bacteria that causes acne. The research was an experimental study by conducting an antibacterial effectiveness test against Staphylococcus epidermidis bacteria. The results of this research are that the combination of meniran herb extract and starfruit can inhibit the growth of Staphylococcus bacteria. A 1:3 combination of starfruit leaf extract (Averrhoa bilimbi L.) and meniran herb (Phyllanthus niruri L.) is effective in inhibiting the growth of Staphylococcus epidermidis bacteria 8.568 mm (Medium).